Build a CI/CD pipeline. (LiveLessons (Indianapolis, Ind.), 2023)
Approximately 8 Hours of Video Instruction If your development team is still dealing with manual and repetitive build- or deployment-related tasks, this course is for you. Overview Software is at the center of our world and touches nearly everything we do. The world depends on great software and access to features at the speed of innovation. Agile processes and mindsets help teams build features iteratively and get feedback quickly to apply learning and correct courses; however, without concepts like DevOps to remind us of what's possible, feedback and innovation hit a dead end or an unnatural pause. To consider yourself or your team truly agile, you must embrace the concept of continuous delivery in its fullness. Continuous delivery is not a goal but a direction. By walking in the direction of continuous delivery, you get closer and closer on a daily basis to reaching a cadence where features and feedback truly move to users at the speed of innovation. Continuous Delivery is at the core of DevOps. About the Instructor Byron Sommardahl is a 30+ year veteran in software development, and his passion for great code and innovative products has never diminished. He went from floundering junior to sought-after senior and on to architect and CTO. Byron helped found and lead as many as 10 simultaneous projects. He has gathered a great deal of valuable knowledge in product ownership and agile engineering. His background in quality software development, project management, and expert product ownership has given him the knowledge to lead his teams and his clients to consistent success. That's why he started the Dev Amplifier Coaching Program, a weekly coaching community and accountability program designed to help you find and close your gaps in knowledge. Learn How To Influence development teams and stakeholders toward continuous delivery and improvement Write more maintainable scripts that enable CI/CD Instruct CI/CD systems using YAML notation Integrate your code automatically and continuously Automate deployment and verification of working software Inform team leadership with meaningful metrics Who Should Take This Course Software developers IT professionals Site reliability engineers (SRE) Course Requirements Scripting or programming skills Experience with Git Experience in deploying web-based projects to hosting providers An AWS account (free tier is okay) A GitHub account Some experience with agile software development and project management is nice Lesson Descriptions Lesson 1, "Delivering Value Consistently": This lesson defines CI/CD and Continuous Delivery, discuses Continuous Delivery as a direction and culture influencer instead of a just set of tools, and explains how to use metrics as a change agent to influence organizational culture. Lesson 2, "Foundations of Sound CI/CD": This lesson teaches scripting options and how to manage them. It also covers YAML syntax and its application in print scenarios in the CI/CD world. Lesson 3, "Continuous Integration": This lesson teaches teams using CI/CD how to shorten feedback loops by failing fast. It also shows how to test various components of Continuous Integration in preparation for completing the artifact build. Lesson 4, "Continuous Deployment": This lesson builds on Continuous Integration teachings in previous lessons by adding technologies and components of Continuous Deployment to move the artifact into the cloud or into a server for public consumption. This lesson also discusses advanced triggering methods to prompt old build jobs to start at different times and for different reasons. It also covers different reusable actions. Lesson 5, "Deployment Strategies": This lesson unpacks different ways to think about deployments. It covers popular patterns and strategies for deploying distributive systems, as well as how to plan a refactor or new implementation. Lesson 6, "Infrastructure Management": This lesson discusses advanced CI/CD practices, such as directing the infrastructure management tool that is best for you and your team, spinning up and tearing down infrastructure in response to rollbacks, and implementing all of this within your CI/CD pipeline. Lesson 7, "Configuration Management": This lesson shows how to integrate configuration management tools into your CI/CD pipeline to enable automation. It discusses how to define your configuration changes ahead of time so that they can be stored in your source control alongside your code, and how to use scripting to deploy changes to remote machines. Lesson 8, "Continuous Delivery": This lesson discusses where DevOps fits in the greater organizational culture and Continuous Delivery at large, as well as cultural changes necessary to keep Continuous Delivery alive and how to measure the adoption of that change. About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Prentice Hall, Sams, and Que. Topics include IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.